Efficient cocktail chemotherapy by co-delivery of a hydrogen sulfide-releasing aspirin prodrug and paclitaxel via single nanoparticles. Issue 22 (28th February 2017) - Cai, Lulu; He, Lin; Wang, Yan; Zhong, Jian; Zhao, Chengjian; Zeng, Shi; Yu, Jiying; Bian, Yuan; Wei, Yuquan; Cai, Wei; Long, Enwu; Jiao, Pengcheng; et al.
Abstract : A cocktail composed of hydrogen sulfide-releasing aspirin (HS-ASP) and paclitaxel (PTX) in a single delivery system was formulated and provides a promising platform for the cocktail treatment of non-small cell lung cancer. Abstract : Cocktail treatment has become an effective multidrug medication therapy for many diseases, because of the additive or synergistic effect of each medicine and relief from adverse effects of drugs. Nanotechnology offers an unparalleled opportunity for co-delivery strategies with the ability to simultaneously release various drugs and controllably unify the pharmacokinetics. In this work, we formulated a cocktail composed of hydrogen sulfide-releasing aspirin (HS-ASP) and paclitaxel (PTX) in a single delivery system, which is fabricated by a biodegradable block copolymer ( i.e., methoxy poly(ethylene glycol)–polycaprolactone). The resulting drug cocktail-loaded nanoparticles possess small and narrow size distribution (∼44 nm), high dual-drug encapsulation efficiency, pH-sensitivity and simultaneous drug release capability. The co-delivery of HS-ASP and PTX has significantly decreased the IC50 value of PTX on LL/2 cells by 17.7-fold compared with single free PTX and by 5.4-fold compared with PTX NPs. Meanwhile, its cellular uptake is improved by 2.67-fold compared with free HS-ASP/FITC-PTX, and it enhanced the cellular apoptosis (53.62%) as well as the cell cycle blocking at G2 /M phase (47.9%) relative to other formulations. Confocal laser scanning results show that HS-ASP inhibited the mitosis of LL/2 cells, thereby sensitizing the cells to the tubulin disruption effect, which is a major apoptosis mechanism of PTX. Overall, such a combinational and controlled release strategy is expected to hold great potential for clinical use in cancer therapy.